2023
DOI: 10.1515/cclm-2023-0577
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte distribution width as an early predictor of short-term outcome in adult patients with sepsis

Yin Liu,
Ruizhi Wang,
Shihua Zhong
et al.

Abstract: Objectives Monocyte distribution width (MDW) is a quantitative measurement of monocyte anisocytosis and has been proposed as an efficient marker for early sepsis detection. This study aimed to assess the prognostic potential of MDW in septic patients. Methods In this study, a total of 252 adult septic patients were enrolled. Demographic, clinical, and laboratory finding including MDW and traditional inflammatory biomarkers de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, MDW was superior to CRP and WBC for this purpose. Moreover, MDW was found to serve as a prognostic predictor of sepsis in ICU patients [35,36].…”
mentioning
confidence: 98%
“…However, MDW was superior to CRP and WBC for this purpose. Moreover, MDW was found to serve as a prognostic predictor of sepsis in ICU patients [35,36].…”
mentioning
confidence: 98%
“…Human monocytic cells in circulation can be categorized into three subsets, each showing different percentages in various diseases ( 12 ). During inflammatory conditions like sepsis ( 13 , 14 ), viral infection ( 15 , 16 ), and other inflammatory diseases ( 17 , 18 ), the changes in the number, volume, and function of monocytes in these subsets differ. Recent research has shown that MDW has been utilized for the early detection of sepsis ( 19 ), with MDW levels increasing with the severity of the condition ( 11 ).…”
Section: Introductionmentioning
confidence: 99%